A Community Education-Based Waste Management System: Addressing Urbanization and the Impacts of Climate Change in Makassar - Muh. - Syukri; Mulkhairi ikram; andi akbar; Muhammad Isnan Rasyidi; Wina Ayu Giswanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze a waste management system based on public education in addressing urbanization and the impacts of climate change in Makassar City. Increasing urbanization has led to an increase in the volume of household waste and increasing pressure on the urban environment, particularly in Manggala District, the location of the Tamangapa Final Disposal Site (TPA). This study used a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Research informants consisted of the Manggala District Government, waste bank managers, PT Pegadaian, and the community. The results showed that waste management based on public education is carried out through a collaborative governance approach between the government, the private sector, and the community through the Waste Bank and